Rice husk ash modified high calcium fly ash recycled aggregate geopolymer concrete, preparation method and application thereof
Patent Information
- Application Number
- CN202611027734.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]为了克服上述现有技术的缺点,本发明的目的在于提供一种稻壳灰改性高钙粉煤灰再生骨料地聚物混凝土及其制备方法和应用,用以解决再生骨料地聚物混凝土强度偏低、孔隙率较大、吸水率较高的问题,并在不采用纳米二氧化硅的条件下,实现与其相近的增强效果
本发明提供了一种稻壳灰改性高钙粉煤灰再生骨料地聚物混凝土,通过掺入稻壳灰调控地聚物体系硅铝摩尔比,实现对高钙粉煤灰再生骨料地聚物混凝土的性能优化。本发明采用稻壳灰替代纳米二氧化硅作为富硅改性材料,原料属于农业副产物,来源广泛、成本低廉且环境友好,可避免纳米二氧化硅制备能耗高、成本高的缺陷,在达到相近增强效果的前提下有效降低材料整体成本,更适合规模化工程应用。在适宜掺量下,稻壳灰可有效优化地聚物凝胶的三维网络结构,显著提升再生骨料地聚物混凝土的早期与后期抗压强度,同时对劈裂抗拉强度、抗折强度具有一定改善作用,能够有效弥补再生骨料表面附着老砂浆、界面过渡区薄弱带来的力学性能损失,最优配比下的力学性能可接近天然骨料地聚物混凝土水平。稻壳灰还可填充基体内部孔隙,明显降低材料的孔隙率与吸水率,提升基体致密性,有利于改善混凝土的长期耐久性能。与纳米二氧化硅改性方案相比,稻壳灰对混凝土拌合物的工作性负面影响更小,可在保障力学性能的同时维持较好的施工流动性;且经高温作用后,稻壳灰改性试样的残余强度表现更稳定,高温性能更具优势。此外,本发明可同步消纳高钙粉煤灰、稻壳灰与废弃混凝土再生骨料多类固体废弃物,实现多源固废的协同资源化利用,减少天然石料与胶凝材料的消耗,契合绿色建筑材料的发展方向,兼具良好的经济效益、环境效益与工程推广价值。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials and solid waste resource utilization technology, specifically relating to a rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete, its preparation method and application. Background Technology
[0002] Traditional silicate cement concrete preparation processes are energy-intensive and produce large carbon emissions, making them unsuitable for the green and low-carbon development needs of the construction industry. Fly ash-based polymer materials can partially or completely replace cement as a cementitious component. With their low-carbon emission characteristics and excellent material properties, they have become an important development direction for low-carbon building materials. High-calcium fly ash, in particular, can achieve setting and hardening at room temperature, making it suitable for on-site casting applications and possessing high promotional value. Meanwhile, waste concrete from building demolition can be crushed and screened to produce recycled coarse aggregate. Replacing natural coarse aggregate in concrete with recycled aggregate can reduce the consumption of natural stone mining and alleviate the environmental pressure caused by construction waste accumulation, representing an important pathway for the resource utilization of construction waste.
[0003] However, in existing technologies, recycled aggregates have old mortar adhering to their surface, resulting in high porosity and water absorption. When applied to geopolymer concrete, this easily leads to a loose internal matrix structure and a weak interfacial transition zone between the aggregate and the matrix, consequently causing a decrease in the compressive strength, tensile strength, and durability of the concrete, thus limiting the engineering application range of recycled aggregate geopolymer concrete. Existing research shows that increasing the SiO2 / Al2O3 molar ratio of the geopolymer system can optimize the gel network structure and improve the material's density and mechanical strength. Currently, nano-silica is often used as a silicon-rich modifying component to achieve the above effects, but the preparation cost of nano-silica is high, and the production energy consumption is large, which is not conducive to the large-scale promotion of the material. Rice husk ash, as an agricultural by-product, is widely available and rich in active silica, possessing the potential to be a low-cost, green silicon source modifying material.
[0004] Therefore, developing a technical solution to modify high-calcium fly ash recycled aggregate geopolymer concrete using rice husk ash, so that the material has good workability, mechanical properties and resource utilization value, has important practical significance and engineering application value. Summary of the Invention
[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete, its preparation method and application, so as to solve the problems of low strength, large porosity and high water absorption of recycled aggregate geopolymer concrete, and to achieve a similar strengthening effect without using nano silica.
[0006] To achieve the above objectives, the present invention employs the following technical solution: This invention provides a rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete, comprising high-calcium fly ash, alkali activator, recycled coarse aggregate, fine aggregate and rice husk ash; The mass ratio of the alkaline activator to high-calcium fly ash is 0.6, and the alkaline activator is composed of a sodium hydroxide solution and a sodium silicate solution with a mass ratio of 1:1. The amount of rice husk ash added is 1.2% to 3.6% of the mass of high-calcium fly ash, so that the molar ratio of SiO2 to Al2O3 in the concrete system is controlled within the range of 4.17 to 4.33. The mass ratio of the recycled coarse aggregate to the high-calcium fly ash is (1.8-2.4):1, and the mass ratio of the fine aggregate to the high-calcium fly ash is (0.9-1.2):1.
[0007] In one embodiment, the mass ratio of the recycled coarse aggregate to the high-calcium fly ash is 97:45, and the mass ratio of the fine aggregate to the high-calcium fly ash is 10:9.
[0008] In one embodiment, the recycled coarse aggregate is obtained by crushing and screening waste concrete, with a particle size of 5 to 20 mm; the fine aggregate is natural river sand.
[0009] In one embodiment, the concentration of the sodium hydroxide solution is 10 mol / L; the sodium silicate solution contains 30.3 wt% SiO2, 12.3 wt% Na2O, and 57.3 wt% H2O.
[0010] In one embodiment, the amount of rice husk ash is 1.2% of the mass of high-calcium fly ash.
[0011] In one embodiment, the concrete has a compressive strength of not less than 38 MPa at 28 days, a porosity of not more than 11.5%, and a water absorption rate of not more than 5.0%.
[0012] This invention also provides a method for preparing rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete, comprising the following steps: (1) Dry mix high-calcium fly ash and rice husk ash evenly to obtain a mixed powder; (2) Add sodium hydroxide solution to the mixed powder and stir for 5 min; (3) Add recycled coarse aggregate and fine aggregate, and continue stirring for 5 min; (4) Add sodium silicate solution and stir for 5 min to obtain a mixture; (5) Pour the mixture into a mold, and after demolding, wrap it with plastic film and cure it at room temperature until the specified age.
[0013] In one embodiment, the specified age is 7 days, 28 days, or 90 days.
[0014] This invention also provides an application of rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete in the preparation of load-bearing components for building structures or road engineering materials.
[0015] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a rice husk ash-modified high-calcium fly ash recycled aggregate geopolymer concrete. By incorporating rice husk ash to regulate the silicon-aluminum molar ratio of the geopolymer system, the performance of the high-calcium fly ash recycled aggregate geopolymer concrete is optimized. This invention uses rice husk ash instead of nano-silica as a silicon-rich modifying material. The raw material is an agricultural byproduct, widely available, inexpensive, and environmentally friendly, avoiding the high energy consumption and cost of nano-silica preparation. While achieving similar reinforcing effects, it effectively reduces the overall material cost, making it more suitable for large-scale engineering applications. At appropriate dosages, rice husk ash can effectively optimize the three-dimensional network structure of the geopolymer gel, significantly improving the early and later compressive strength of the recycled aggregate geopolymer concrete. It also has a certain improvement effect on splitting tensile strength and flexural strength, effectively compensating for the mechanical property losses caused by old mortar adhering to the surface of the recycled aggregate and the weak interfacial transition zone. The mechanical properties under optimal proportions can approach the level of natural aggregate geopolymer concrete. Rice husk ash can also fill the pores inside the matrix, significantly reducing the porosity and water absorption rate of the material, improving the density of the matrix, and thus improving the long-term durability of concrete. Compared with nano-silica modification, rice husk ash has less negative impact on the workability of concrete mixtures, maintaining good construction fluidity while ensuring mechanical properties; and after high-temperature treatment, the residual strength of rice husk ash modified samples is more stable, demonstrating superior high-temperature performance. Furthermore, this invention can simultaneously utilize high-calcium fly ash, rice husk ash, and recycled aggregates from waste concrete, achieving synergistic resource utilization of multi-source solid waste, reducing the consumption of natural stone and cementitious materials, aligning with the development direction of green building materials, and possessing good economic, environmental, and engineering promotion value. Detailed Implementation
[0016] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0017] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0018] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0019] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0020] This invention provides a rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete, its preparation method, and its application. High-calcium fly ash is used as the main cementitious precursor, a mixture of sodium hydroxide solution and sodium silicate solution is used as an alkali activator, recycled coarse aggregate replaces natural coarse aggregate as coarse aggregate, and rice husk ash is incorporated as a silicon source modifier. The silicon-rich modifier increases the SiO2 / Al2O3 molar ratio of the system. By controlling the proportion of rice husk ash added, the SiO2 / Al2O3 molar ratio of the geopolymer system is adjusted to within the range of 4.17–4.33. When the silicon-aluminum molar ratio is approximately 4.17, the material exhibits optimal overall performance in terms of workability, mechanical properties, and density.
[0021] On one hand, the raw materials used in this invention include high-calcium fly ash, alkali activator, rice husk ash, recycled coarse aggregate, and fine aggregate. High-calcium fly ash is the core aluminosilicate precursor of the system and is the main raw material for the formation of geopolymer gel. The alkali activator is a compound of sodium hydroxide solution and sodium silicate solution with a concentration of 10 mol / L, wherein the sodium silicate solution has a component ratio of approximately 30.3 wt% SiO2, approximately 12.3 wt% Na2O, and approximately 57.3 wt% H2O. Rice husk ash is ball-milled and refined as a silicon-rich modifying material to adjust the silicon-aluminum molar ratio of the system and optimize the gel network structure. The recycled coarse aggregate is obtained by crushing and screening waste concrete and is used to replace natural coarse aggregate to realize the resource utilization of construction solid waste. The fine aggregate is natural river sand.
[0022] This material uses rice husk ash as a silicon-rich modifier instead of nano-silica, offering advantages such as wide availability, low cost, and environmental friendliness. At appropriate dosages, rice husk ash can significantly improve the early and later compressive strength of recycled aggregate geopolymer concrete. Rice husk ash can reduce material porosity and water absorption, improving matrix density. Compared to nano-silica, rice husk ash has less negative impact on workability and exhibits more stable residual strength after high temperatures. It enables the synergistic resource utilization of high-calcium fly ash, rice husk ash, and recycled aggregates, making it suitable for the development of green building materials.
[0023] The formulation of this invention is designed with the reaction characteristics and modification effect of geopolymers as the core: the mass ratio of alkali activator to high-calcium fly ash is fixed at 0.6, and the mass ratio of sodium silicate solution to sodium hydroxide solution in the compound alkali activator is 1:1; the SiO2 / Al2O3 molar ratio of the system is precisely adjusted by adjusting the amount of rice husk ash added. The preferred amount of rice husk ash is 1.2% to 3.6% of the mass of high-calcium fly ash, and more preferably 1.2%.
[0024] On the other hand, a method for preparing rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete is also provided, including the following steps: First, put high-calcium fly ash and rice husk ash into a mixer and dry mix until uniform to obtain a mixed powder. Then, sodium hydroxide solution was added to the mixed powder, and the mixture was stirred for about 5 minutes to allow the powder to be initially dispersed and wetted and to undergo an early depolymerization reaction. Add recycled coarse aggregate and natural river sand, and continue stirring for about 5 minutes to ensure that the aggregate and powder are fully and evenly mixed. Then add sodium silicate solution and stir continuously for about 5 minutes to obtain a homogeneous mixture with good workability; Finally, the mixture is poured into a mold and vibrated to shape it. After the sample is demolded, it is sealed with plastic film and cured at room temperature until the specified age.
[0025] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0026] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0027] Five groups of samples were set up for comparative experiments, including two control groups and three modified groups with different amounts of rice husk ash. The unit volume proportion parameters of each group are shown in the table below:
[0028] Note: The units for material usage and mass per unit volume in the table are kg / m³. 3 The SiO2 / Al2O3 ratio is a dimensionless molar ratio.
[0029] Note: Three additional control groups of nano-silica (1nS, 2nS, 3nS) were set up, with the same silicon-to-aluminum ratio as the rice husk ash group, to compare the modification effect.
[0030] Performance Testing and Results Analysis (a) Workability The slump spread was used to characterize the workability of the mixture. The test results for each group of samples are as follows:
[0031] Test results show that the introduction of recycled aggregate can improve the fluidity of the mixture. The slump expansion of the recycled aggregate control group is significantly higher than that of the natural aggregate control group. The fluidity of the mixture decreases after the addition of rice husk ash, but the decrease is significantly smaller than that of the nano-silica modified group. This indicates that rice husk ash has a lower negative impact on the workability of concrete and is more conducive to on-site construction applications.
[0032] (ii) Compressive strength The compressive strength of each group of specimens was tested at 7d, 28d, and 90d, and the results are shown in the table below:
[0033] Strength results show that the use of recycled aggregate reduces the compressive strength of geopolymer concrete at all ages. The addition of an appropriate amount of rice husk ash significantly improves both early and late-stage compressive strength. The 28-day compressive strength of the 1.2RHA group reaches 38.1 MPa, which is comparable to the nano-silica modified group with the same Si / Al ratio (38.2 MPa) and close to the strength level of the natural aggregate control group. Overall, the system exhibits the best compressive strength when the SiO2 / Al2O3 molar ratio is approximately 4.17.
[0034] (III) Splitting tensile strength and flexural strength The splitting tensile strength and flexural strength of each group of specimens at 28 days of age were tested, and the results are as follows:
[0035] The results showed that rice husk ash has a certain effect on improving the splitting tensile strength of recycled aggregate geopolymer concrete, which can be increased from 2.5MPa to 2.7MPa under the optimal mix ratio. The flexural strength is also slightly improved, but the overall improvement is weaker than that of the compressive strength.
[0036] (iv) Porosity and water absorption The porosity and water absorption of each group of samples were tested at 28 days to characterize the compactness and durability of the materials. The results are as follows:
[0037] Test results show that recycled aggregates significantly increase the porosity and water absorption of concrete, and deteriorate the density of the matrix. The addition of rice husk ash can effectively fill the internal pores and significantly reduce the porosity and water absorption of the material. Among them, the 1.2RHA and 2.4RHA groups have the most outstanding effect on improving density, which is close to the effect of nano-silica modification.
[0038] (v) Residual compressive strength after fire The residual compressive strength of 28-day-old specimens after being subjected to high-temperature treatment for 30 min and 60 min was tested, and the percentage of residual strength was calculated. The results are as follows:
[0039] High-temperature performance test results show that both rice husk ash and nano-silica can improve the mechanical properties of the material at room temperature, but will slightly reduce the proportion of residual strength after high temperature. Overall, the high-temperature residual strength of the rice husk ash modified group is slightly better than that of the nano-silica modified group, and the high-temperature stability is more advantageous.
[0040] In summary, the introduction of recycled aggregates leads to a decrease in the compressive, tensile, and flexural strengths of geopolymer concrete, while increasing porosity and water absorption, but improving the flowability of the mixture. Rice husk ash, as a silica-rich modifier, effectively increases the SiO2 / Al2O3 molar ratio of the system, promotes the optimization of the geopolymer gel network structure, and exerts a micro-aggregate filling effect, thereby significantly improving the mechanical strength of concrete and improving matrix density. When the SiO2 / Al2O3 molar ratio is approximately 4.17, the material exhibits the best overall performance, with a 28-day compressive strength of 38.1 MPa in the 1.2RHA group, a significant improvement over the recycled aggregate control group. Overall, the reinforcing and modifying effect of rice husk ash is similar to that of nano-silica, but with less negative impact on workability. Furthermore, the raw material is widely available and lower in cost, making it a more valuable green modifier for wider application. It should be noted that the residual strength of all samples decreased significantly under fire conditions, indicating that there is still room for further optimization of the high-temperature performance of this type of geopolymer concrete.
[0041] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of this invention.
Claims
1. A rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete, characterized in that, Including high-calcium fly ash, alkali activator, recycled coarse aggregate, fine aggregate and rice husk ash; The mass ratio of the alkali activator to high-calcium fly ash is 0.6, and the alkali activator is composed of a sodium hydroxide solution and a sodium silicate solution with a mass ratio of 1:
1. The amount of rice husk ash added is 1.2% to 3.6% of the mass of high-calcium fly ash, so that the molar ratio of SiO2 to Al2O3 in the concrete system is controlled within the range of 4.17 to 4.
33. The mass ratio of the recycled coarse aggregate to the high-calcium fly ash is (1.8-2.4):1, and the mass ratio of the fine aggregate to the high-calcium fly ash is (0.9-1.2):
1.
2. The rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete according to claim 1, characterized in that, The mass ratio of the recycled coarse aggregate to the high-calcium fly ash is 97:45, and the mass ratio of the fine aggregate to the high-calcium fly ash is 10:
9.
3. The rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete according to claim 1, characterized in that, The recycled coarse aggregate is obtained by crushing and screening waste concrete, with a particle size of 5-20 mm; the fine aggregate is natural river sand.
4. The rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete according to claim 1, characterized in that, The concentration of the sodium hydroxide solution is 10 mol / L; the sodium silicate solution contains 30.3 wt% SiO2, 12.3 wt% Na2O, and 57.3 wt% H2O.
5. The rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete according to claim 1, characterized in that, The amount of rice husk ash added is 1.2% of the mass of high-calcium fly ash.
6. The rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete according to claim 1, characterized in that, The concrete has a compressive strength of not less than 38 MPa at 28 days, a porosity of not more than 11.5%, and a water absorption rate of not more than 5.0%.
7. A method for preparing rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1, dry mix high-calcium fly ash and rice husk ash evenly to obtain mixed powder; S2, sodium hydroxide solution, recycled coarse aggregate and fine aggregate, and sodium silicate solution are added sequentially to the mixed powder to obtain a mixture; S3. The mixture is poured into a mold, demolded, wrapped in plastic film, and cured at room temperature until the specified age.
8. The method for preparing rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete according to claim 7, characterized in that, In S2, during the sequential addition of sodium hydroxide solution, recycled coarse aggregate and fine aggregate, and sodium silicate solution, the mixture is stirred continuously for 5 minutes after each addition.
9. The method for preparing rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete according to claim 7, characterized in that, The specified age is 7 days, 28 days, or 90 days.
10. The application of rice husk ash modified high-calcium fly ash recycled aggregate geopolymer concrete as described in any one of claims 1 to 6 in the preparation of load-bearing components of building structures or road engineering materials.